Involvement of B cells in the development of systemic sclerosis - Yoshizaki, Ayumi; Fukasawa, Takemichi; Ebata, Satoshi; Yoshizaki-Ogawa, Asako; Sato, Shinichi (Frontiers in Immunology, 2022)
Systemic sclerosis (SSc) is a rare intractable systemic disease that causes fibrosis and vasculopathy against a background of autoimmune abnormalities. Although the etiology is not yet fully understood, the type of autoantibodies detected in SSc is closely associated with disease severity and prognosis, supporting those autoimmune abnormalities play an important role in the pathogenesis of SSc. Although the direct pathogenicity of autoantibodies is unknown, B cells, one of the lymphocytes responsible for their production, are thought to play an important role in the development of SSc. B cells are composed of diverse subsets and have been shown to have diverse functions at the same time. Indeed, many previous studies have shown that B cells are involved in the development of SSc through a variety of functions. Furthermore, a number of clinical studies have been conducted in which B-cell depletion therapy has been tried for SSc, and many of these studies have found B-cell depletion therapy to be effective for SSc. However, the involvement of B cells in pathogenesis is complex, as they not only promote inflammation but can also play an inhibitory role. This article outlines the role of B cells in the development of SSc, including the latest research.